Global Citizenship literacy: Investigating Awareness Level of Prospective Teachers of Punjab Concerning Rights - Saliha Khan (IJLTP, 2025)
Global citizens strive to promote global justice and build a more secure, just, and sustainable world that upholds human rights. This study explores prospective teachers' views on global citizenship literacy concerning rights. This study used a qualitative exploratory research design with purposive sampling. Data was collected through an open-ended questionnaire to measure global citizenship education relating to rights. The data was obtained from 203 prospective teachers of graduating semesters at public sector colleges and universities including Rawalpindi and Islamabad, in Punjab. The data was analyzed through thematic analysis. Codes were used to develop themes to generate a result with mixed method analysis such as several respondents and their percentage the data thematic analysis shows that although fewer respondents are aware of rights and global citizenship education, their awareness is not much about global citizenship concerning rights. The concepts of social justice, human rights, cultural diversity, global cultural links, and global citizenship literacy may be incorporated into the curriculum by policymakers and interactive teaching methods may be followed to enhance global citizenship literacy.